KESIAPAN IMPLEMENTASI REKAM MEDIS ELEKTRONIK DI POLI RAWAT JALAN PUSKESMAS MALAMBORA WANI MENGGUNAKAN METODE DOQ-IT - Aulia Salmah,; Rian Andriani,; Kahar Mulyani, (Journal of Innovation Research and Knowledge, 2025)
The presence of information technology affects the effectiveness and efficiency of health service delivery in Indonesia. The application of health information technology in the health sector that is currently trending globally is Electronic Medical Records (EMR). Improvement of EMR management has begun to be implemented in several health facilities including in Community Health Centers. Given the complexity of the challenges for implementing EMR, it is necessary to assess the readiness of EMR implementation. The purpose of this study was to determine the readiness of the implementation of electronic medical records in the Outpatient Clinic of the Malambora Wani Community Health Center. This study used a qualitative descriptive method with a case study design. The subjects consisted of 8 employees selected using purposive sampling techniques. Data collection was carried out by interview and observation. Readiness analysis was carried out using the DOQ-IT method with four components, namely human resources, organizational work culture, leadership governance, and technology infrastructure. The results of the study showed that the Malambora Wani Community Health Center in terms of readiness to implement EMR from the aspect of Human Resources was considered very ready, from the aspect of Organizational Work Culture it was very ready, and Leadership Governance was also considered very ready. Meanwhile, from the aspect of Technology Infrastructure it was considered quite ready